Musikdramatik, rum og liturgi: Dronning Ingeborgs lovsang i teatrets og liturgiens rum - Petersen, Nils Holger (Kirkehistoriske Samlinger, 1995)
»The Praises of Queen Ingeborg« is a music drama recently written by the author of the article. The article forms partly a presentation of this so-called liturgical opera which is based on an episode from the Danish-French medieval history and partly a discussion of the genre of the work in between opera and liturgy. »Queen Ingeborg« was composed in 1991 (and performed in 1992) while the author was working on a Ph.D. dissertation on the medieval Latin music drama, a medieval genre within the liturgy. The author reviews the history of the Danish princess Ingeborg (daughter of king Valdemar I of Denmark) who in 1193 was married to the French king Philip II August. The day after the wedding he rejected his bride and - as the Danish delegation refused to take her back to Denmark - kept her confined under more or less severe circumstances through 20 years (in spite of a papal interdict in 1200) until he - surprisingly - took her back officially as his queen in 1213. The opera follows the historical facts closely interpolating invented persons into the known circumstances. The opera tries to establish both a liturgical and a theatrical space so that the action unfolds out of celebrational elements while these loops of action in the end again conclude in celebrations. The liturgical premises are, of course, radically transformed since the Middle Ages and the author briefly discusses in what sense such a work can be said to function as a celebration. The medieval genre of the so-called liturgical drama and its function in between representational ceremony and liturgical celebration is discussed as a background for the account of the specific traits of »Queen Ingeborg« that characterize the genre of this modern work. Since the operatic genre was established around 1600 only few music dramas have taken up the liturgico-dramatic genre; some isolated works by Mozart, Benjamin Britten and Peter Maxwell Davies are mentioned in passing.